How Difficult is 1+1? A Phenomenological Study of High School Students Struggling in Mathematics - Datu Yuri Camenda; Cybelle Angela Gaba; Nazirev Lacord; Dania Natango; Alecshane Pabl; Hassanal Abusam (Universitas Pendidikan Indonesia (UPI), 2021)
The study’s purpose was to understand and elaborate the problems of those students who were having difficulty in mathematics, as well as to help them in boosting up their self-assurance when playing out the subject. This study sought to answer the following questions: (1) What are the problems that the students encounter in Mathematics? (2) Why are they having difficulty in Mathematics? (3) What are the possible ways for them to cope up with Mathematics? We used the qualitative study to support the analysis, particularly phenomenological research. The method used to gather data for the study was the interview with the use of guide questionnaires. A purposive sampling technique was used to gather participants in the study. The participants were four students of Sultan Kudarat State University (SKSU) – Laboratory High School. This research also employed a triangular method of interview. The participants had been through different struggles in mathematical subjects. We came up with themes as different perspective was shared. The participants felt bad for their performance with mathematics. However, they also recognized that self-reliance might be a better way to cope up in the course of mathematics. All of the participants displayed maturity and liberality in the said problems for all of their answers. This study can be a great instrument to help those students who were sunken beneath in having difficulties in Mathematics.